Fabrication and characterization of monolayer and few-layer 2D materials - Tan, Coon Siong (2015)
The isolation of 2D materials has attracted much interest in recent years. There are many isolation methods that have been created to study the properties of 2D material. Mechanical exfoliation method has proved to be a successful method to isolate bulk layered materials. In this project, the isolation and characterization of black phosphorus down to few layers thin by using mechanical exfoliation method are presented. Several methods are presented to determine the thickness of few layers black phosphorus such as optical imaging, Raman spectroscopy and AFM. Moreover, field-effect transistor based on few layers black phosphorus was fabricated and characterization of the transistor has been done in this project as well. The FET was found to be like ambipolar transistor as it shows both p type and n type behaviors in the drain current. The high drain current makes black phosphorus has huge potential for application in digital electronics. In addition, it also shows a distinct signature of ohmic contact (metal-BP) due to the drain current varies linearly with small source-drain biases. Lastly, mobility characteristic has been studied followed by recommendations in future work.